(3y+6)/4-(2y-6)/4=(3y)/4

Simple and best practice solution for (3y+6)/4-(2y-6)/4=(3y)/4 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (3y+6)/4-(2y-6)/4=(3y)/4 equation:



(3y+6)/4-(2y-6)/4=(3y)/4
We move all terms to the left:
(3y+6)/4-(2y-6)/4-((3y)/4)=0
We add all the numbers together, and all the variables
(3y+6)/4-(2y-6)/4-(+3y/4)=0
We get rid of parentheses
(3y+6)/4-(2y-6)/4-3y/4=0
We multiply all the terms by the denominator
(3y+6)-(2y-6)-3y=0
We add all the numbers together, and all the variables
-3y+(3y+6)-(2y-6)=0
We get rid of parentheses
-3y+3y-2y+6+6=0
We add all the numbers together, and all the variables
-2y+12=0
We move all terms containing y to the left, all other terms to the right
-2y=-12
y=-12/-2
y=+6

See similar equations:

| 8=-5x14 | | 2x-10=94 | | 3x-5+4=-5+2x | | -2x^2+4x=336 | | 1/2v+2/5=-1/6v-2/5 | | (7x+33)=(12x-17) | | 2x+x-42=0 | | 25t-5t^2=100 | | (3x-9)*3=x | | 4x+9=6-× | | 9x-27=-72x+36 | | 3x-9/6=-12x+6/3 | | x=4/5(x+10 | | 3n=-2 | | 2(x+3)^2=1080 | | 6+k=13 | | (n+2)×180=2160 | | (x+2)×180=2160 | | 2(3x-5=8 | | 2x=7=-38-7x | | (5x+11)=(3x+25) | | 20-2p=-2p-4+4p | | 1=4^2x | | 2(x-3)=3(2x+5)+4(-x+1) | | 1/3^(2x)-12/3x+27=0 | | X-(0.26x)=7000 | | x+0.25x=260 | | 3d-22=2d-2d | | (x+5)=(1/2)(4x) | | 10(x-9)=6x-78 | | r119=70. | | 2(8-3y)^2-17y^2=-60 |

Equations solver categories